Dampak Efisiensi dan Efektivitas Human Resources Information System Pada Human Resources Department PT Kareta Sabila - Indri Guslina (Peneliti.net, 2022)
Each organization always strives to support the routine activities of each human resource related to productivity and performance. The support of activities provided facilitates the human resources/hr department of PT Kareta Sabila in data and information management related to staffing, payroll, attendance and organizational structure. With the right system, workers can update data such as addresses, to other personal affairs using only the app. HRIS at PT Kareta Sabila as a system created to be the answer to HR problems in companies related to human resources involved in it. The use of HRIS becomes effective because it replaces routine tasks performed manually, as well as efficient time, cost and energy. With one software all recorded well and neatly by reducing the risk of manual workmanship and done accurately and evaluation is easily done whenever necessary